Preparation method of coal gangue ceramsite concrete subjected to surface hydrophobic treatment

By treating the surface of coal gangue ceratops with silicone solution, a water-repellent film is formed, which solves the concrete performance problem caused by the high water absorption rate of the ceratops, and significantly improves the mechanical properties and construction properties of the concrete.

CN119528496APending Publication Date: 2025-02-28XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411736087.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The high water absorption rate of coal gangue ceratops leads to excessive loss of slump of concrete mixture, affecting pumping and casting, and pre-wetting treatment will reduce the cylinder pressure strength of the ceratops and the strength of the concrete.

Method used

The surface water-repellent treatment of coal gangue ceratops was performed using silicone solution to form a film of insoluble waterproof polymer compound with several molecules thick, reducing the water absorption rate of the ceratops.

Benefits of technology

Significantly reduce the water absorption rate of coal gangue ceratops, improve the mixture performance of concrete, improve the compressive strength and split tensile strength of cubes, and enhance the overall performance of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528496A_ABST
    Figure CN119528496A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of coal gangue ceramsite concrete subjected to surface hydrophobic treatment. The method comprises the following steps: 1, preparing an organic silicon hydrophobic dipping solution with the mass percent of 2-6%; step 2, weighing a proper amount of coal gangue ceramsite, and putting the coal gangue ceramsite into the hydrophobic dipping solution prepared in the step 1 for dipping; 3, the impregnation time of the coal gangue ceramsite in the organic silicon impregnation solution is controlled to be 10 s to 1 h; 4, the coal gangue ceramsite obtained after dipping treatment is placed indoors to be naturally dried for 3 days; and 5, preparing the coal gangue ceramsite concrete by using the coal gangue ceramsite subjected to hydrophobic dipping treatment to completely replace coarse aggregate. The organic silicon solution is used for carrying out dipping treatment on the coal gangue ceramsite, a hydrophobic layer is formed on the surface of the ceramsite, and therefore the water absorption rate of the coal gangue ceramsite is reduced, and the method has the advantages of being easy and convenient to operate and convenient to implement and popularize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete preparation, and in particular to a method for preparing surface hydrophobic treated coal gangue ceramsite concrete. Background Art

[0002] As a solid waste, coal gangue has clay properties because it contains a large amount of silicon dioxide, iron oxide and aluminum oxide. About 40% of it can be burned into coal gangue ceramsite, which can be added to concrete as a lightweight aggregate to prepare an apparent density of less than 1950kg / m 3 Gangue ceramsite lightweight aggregate concrete. Gangue ceramsite is a loose porous material. When used as lightweight aggregate, it has a large water absorption capacity. Under the condition of the same working performance, it requires a higher water-cement ratio than ordinary concrete. The water absorption process of lightweight aggregate is most intense within the last 10 to 15 minutes of concrete mixture preparation, and the amount of water absorption depends on the water-cement ratio of the concrete mixture. The larger the water-cement ratio of the concrete mixture, the greater the amount of water absorbed by the lightweight aggregate from the mixture. However, this is not conducive to the application of lightweight aggregate concrete, because fluid concrete and premixed concrete technology are currently widely used. Fluid lightweight aggregate concrete may cause excessive slump loss of concrete mixture due to its high water absorption rate, affecting pumping and pouring, and segregation of concrete mixture due to improper construction treatment such as long-distance transportation, excessive self-fall height during pouring, and long vibration time.

[0003] At present, pre-wetting treatment is mainly used in engineering applications to reduce the problems caused by excessive water absorption of ceramsite.

[0004] For example, in Li Mengjuan. Study on the influence of ceramsite properties and pretreatment on the performance of ceramsite concrete [J]. Northern Architecture, 2024, 9(03): 104-108, it is believed that prewetting is more effective in solving the problem, but the cylinder compressive strength of lightweight aggregate that has been prewetted will be significantly reduced, so that the strength of the prepared concrete will also be significantly reduced and the dispersion is larger. If the concrete is mixed with the total water content during use, a large amount of water will be added at one time when high fluidity is required, which will inevitably cause stratification and segregation of the freshly mixed concrete. Therefore, any method and way to reduce the water absorption rate of lightweight aggregate will be conducive to the expansion of the application range of lightweight aggregate concrete and the improvement of its performance. Summary of the invention

[0005] In order to overcome the defects of the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing surface hydrophobic treated coal gangue ceramsite concrete, in which the coal gangue ceramsite is impregnated with an organic silicon solution to form a layer of insoluble waterproof polymer compound with a thickness of several molecules on the surface of the ceramsite, i.e., a mesh organic silicon resin film, so that the wetting angle thereof is changed from less than 90° to greater than 90°, and the ceramsite is changed from hydrophilic to hydrophobic, thereby reducing the water absorption rate of the coal gangue ceramsite. The method has the characteristics of simple operation and easy implementation and promotion.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing surface hydrophobic treated coal gangue ceramsite concrete comprises the following steps:

[0008] Step 1: prepare a 2-6% by mass organic silicon hydrophobic impregnation solution;

[0009] Step 2: Weigh an appropriate amount of coal gangue ceramsite and put it into the hydrophobic impregnation solution prepared in step 1 for impregnation;

[0010] Step 3: Control the immersion time of the gangue ceramsite in the organosilicon impregnation solution to be 10s to 1h;

[0011] Step 4: Place the impregnated coal gangue ceramsite in the room to dry naturally for 3 days;

[0012] Step 5: Use the hydrophobic impregnation treated coal gangue ceramsite to completely replace the coarse aggregate to prepare the coal gangue ceramsite concrete.

[0013] In step 1, the organic silicon hydrophobic solution used is an aqueous sodium methylsiliconate hydrophobic solution produced by Lianxiang, and its chemical formula is (CH3)3SiONa.

[0014] In step 2, in order to control the impregnation time, the gangue ceramsite is placed in a plastic basket with a filter screen for impregnation treatment. The mesh aperture is 3 mm. The physical properties of the gangue ceramsite are a particle size of 5 to 16 mm and a bulk density of 900 to 950 kg / m 3 , apparent density 1300~1330kg / m 3 , 1h water absorption rate 6.0%~6.5%, cylinder pressure strength 5.0~6.0MPa.

[0015] In step 3, the gangue ceramsite is impregnated with an organosilicon solution to form a layer of insoluble waterproof polymer compound with a thickness of several molecules on the surface of the ceramsite, i.e., a mesh organosilicon resin film, so that the wetting angle thereof changes from less than 90° to greater than 90°, and the ceramsite changes from hydrophilic to hydrophobic.

[0016] In the step 5, the LC30 gangue ceramsite concrete is prepared by mixing the hydrophobic impregnation treated gangue ceramsite, cement, fly ash and fine aggregate;

[0017] In step 5, the gangue ceramsite concrete material includes the following raw materials in parts by weight: 352 parts of cement, 88 parts of fly ash, 660 parts of natural river sand, 560 parts of hydrophobic impregnation treated gangue ceramsite, 145 parts of water, and 2.2 parts of polycarboxylic acid water reducer.

[0018] The compressive strength of the gangue ceramsite concrete cube meets the strength design requirements of LC30 lightweight aggregate concrete.

[0019] The preparation of coal gangue ceramsite concrete comprises the following steps: mixing cement, fly ash, natural river sand, coal gangue ceramsite treated with hydrophobic impregnation and polycarboxylate water reducer according to a preset ratio, stirring for 30 seconds, then adding water, stirring for 3 minutes, and obtaining the surface hydrophobic treated ceramsite concrete;

[0020] The vibration time of the surface hydrophobic treated ceramsite concrete during molding should not exceed 5s.

[0021] Beneficial effects of the present invention:

[0022] After the surface of the gangue ceramsite is treated with organic silicon solution for hydrophobicity, compared with the untreated gangue ceramsite, the water absorption rate of the gangue ceramsite treated with the organic silicon solution is reduced by 70% to 80% in 1 hour and by 40% to 50% in 24 hours;

[0023] The present invention can significantly reduce the water absorption rate of coal gangue ceramsite, thereby improving the mixing performance of coal gangue ceramsite concrete. Compared with the ceramsite concrete prepared with untreated ceramsite and pre-wetted ceramsite, the cube compressive strength and splitting tensile strength of the coal gangue ceramsite concrete after the silicone impregnation treatment are both better. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a 24h water absorption trend chart of silicone impregnated ceramsite with different impregnation concentrations and different impregnation times.

[0025] Figure 2 This is a graph showing the effect of different impregnation concentrations on the contact angle of ceramsite.

[0026] Figure 3 This is a trend chart showing the effect of expanded clay treated with different impregnation concentrations on the compressive strength of concrete.

[0027] Figure 4 This is a trend chart showing the effect of expanded clay treated with different impregnation concentrations on the splitting tensile strength of concrete. DETAILED DESCRIPTION

[0028] The present invention will be further described in detail below in conjunction with the accompanying drawings.

[0029] A method for preparing surface hydrophobic treated coal gangue ceramsite concrete comprises the following steps:

[0030] Step 1: prepare a 2-6% by mass organic silicon hydrophobic impregnation solution;

[0031] Step 2: Weigh an appropriate amount of coal gangue ceramsite and put it into the hydrophobic impregnation solution prepared in step 1 for impregnation;

[0032] Step 3: Control the immersion time of the gangue ceramsite in the organosilicon impregnation solution to be 10s to 1h;

[0033] Step 4: Place the impregnated coal gangue ceramsite in the room to dry naturally for 3 days;

[0034] Step 5: Use the hydrophobic impregnation treated coal gangue ceramsite to completely replace the coarse aggregate to prepare the coal gangue ceramsite concrete.

[0035] In step 1, the organic silicon hydrophobic solution used is an aqueous sodium methylsiliconate hydrophobic solution produced by Lianxiang, and its chemical formula is (CH3)3SiONa.

[0036] In step 2, in order to control the impregnation time, the gangue ceramsite is placed in a plastic basket with a filter screen for impregnation treatment. The mesh aperture is 3 mm. The physical properties of the gangue ceramsite are a particle size of 5 to 16 mm and a bulk density of 900 to 950 kg / m 3 , apparent density 1300~1330kg / m 3 , 1h water absorption rate 6.0%~6.5%, cylinder pressure strength 5.0~6.0MPa.

[0037] In step 4, the water absorption rate of the hydrophobic ceramsite after natural drying for 3 days is tested with reference to the light aggregate water absorption rate test method specified in the national standard GB / T17431.2-2010 "Light aggregate and its test method Part 2: Light aggregate test method". The test steps are as follows:

[0038] (1) Take 1 kg of sample and sieve it through a sieve with a mesh size of 2.36 mm. Take the sieve residue and dry it to a constant weight;

[0039] (2) Mix the sample evenly, divide it into three parts, weigh them separately, and then put them into a container filled with water. Press the floating particles into the water. The sample is immersed in water for 1 to 24 hours.

[0040] (3) Take the sample out of the container at 1 h, 3 h, 6 h, and 24 h, drain the water for 1 min to 2 min, then pour it on a wrung wet towel. Hold the two ends of the towel with your hands to make it into a groove shape. Let the ceramsite roll back and forth on the towel 8 to 10 times, then pour it into an enamel dish to make it saturated and dry. Weigh it and calculate its water absorption rate.

[0041] (4) The water absorption rate is calculated according to formula (1):

[0042]

[0043] Where:

[0044] ω a ——Water absorption rate of ceramsite after 1h, 3h, 6h and 24h, %;

[0045] m0——mass of the immersed sample, in grams (g);

[0046] m1——mass of dried sample, in grams (g);

[0047] The arithmetic mean of three measured values ​​was taken as the test result.

[0048] In the step 5, the LC30 gangue ceramsite concrete is prepared by mixing the hydrophobic impregnation treated gangue ceramsite, cement, fly ash and fine aggregate.

[0049] The cement is P·O42.5 produced by Shaanxi Conch Cement Company, which complies with the national standard GB 175-2023. The fly ash is Class II ash, which complies with the national standard GB 1596-2017. The fine aggregate is natural river sand, with a fineness modulus of 2.7 and an apparent density of 2650kg / m 3 , belonging to zone II sand. The admixture is C1029 polycarboxylate water reducer produced by Fuke, with a water reduction rate of 30%.

[0050] In step 5, the gangue ceramsite concrete material includes the following raw materials in parts by weight: 352 parts of cement, 88 parts of fly ash, 660 parts of natural river sand, 560 parts of hydrophobic impregnation treated gangue ceramsite, 145 parts of water, and 2.2 parts of polycarboxylic acid water reducer.

[0051] The compressive strength of the gangue ceramsite concrete cube meets the strength design requirements of LC30 lightweight aggregate concrete.

[0052] The preparation of coal gangue ceramsite concrete comprises the following steps: mixing surface hydrophobic ceramsite, natural river sand, cementitious material and water reducing agent according to a preset ratio, stirring for 30 seconds, then adding water, stirring for 3 minutes, and obtaining the surface hydrophobic ceramsite concrete;

[0053] The surface hydrophobicity treated ceramsite concrete should not be vibrated for more than 5 seconds during molding. Figure 2 It can be seen that the contact angle of the surface of the gangue ceramsite without surface modification is less than 90°, showing hydrophilicity. The contact angles of the gangue ceramsite after impregnation with different concentrations of silicone are all greater than 90°, showing hydrophobicity, and the contact angle increases with the increase of silicone concentration.

[0054] The surface hydrophobic treated ceramsite concrete features include:

[0055] Improved hydrophobicity: Sodium methylsiliconate forms a hydrophobic layer on the surface of ceramsite, which enhances the overall hydrophobicity of concrete. It can reduce the water absorption of concrete in a humid environment, thereby improving its anti-seepage performance.

[0056] Improved performance of the mixture: The water absorption rate of coal gangue ceramsite after hydrophobic treatment is significantly reduced, and the ceramsite will not absorb too much mixing water during the mixing process, thereby improving the fluidity and pumpability of the concrete mixture. In this way, the concrete is easier to pour and shape, which is conducive to improving construction efficiency.

[0057] Improved mechanical properties: The reduced water absorption of expanded clay makes the water-cement ratio at the interface smaller, making the interface transition zone with the cement matrix denser, enhancing the strength of the interface zone, and thus improving the compressive and splitting tensile properties of concrete.

[0058] Embodiment 1:

[0059] Prepare sodium methylsiliconate solutions with mass percentages of 1%, 2%, 4%, 6%, and 8%, weigh 5 parts of 1kg of coal gangue ceramsite, immerse the ceramsite in the prepared solution, take it out after controlling the immersion time of 5 to 10s, let it stand in the filter for 2min to control the excess water, and then place it in the shade indoors for 3d, and then conduct water absorption test, immerse 1kg of naturally dried organic silicon impregnated ceramsite completely in water, take it out at 1h, 3h, 6h, and 24h, and make it into saturated surface dry weight according to the water absorption test method in step 4, and calculate its water absorption, as shown in Table 2. It can be seen from the table that with the increase of the concentration of sodium methylsiliconate solution, the water absorption of ceramsite decreases significantly, among which, the 6% concentration of sodium methylsiliconate impregnation ceramsite has the best effect, and its 1h water absorption rate decreases by 78% and 24h water absorption rate decreases by 54% compared with the untreated ceramsite. Then, a 6% concentration sodium methylsiliconate solution was prepared, and 7 portions of 1 kg of coal gangue ceramsite of equal mass were weighed respectively. The number of solution cycles of 1, 3, 5, and 7 were selected. The immersion treatment and water absorption test steps were the same as above. The effect of different solution cycles on the water absorption of ceramsite was obtained as shown in Table 3. It can be seen that with the increase of the number of solution cycles, the 24h water absorption of ceramsite increased, indicating that the hydrophobic effect of sodium methylsiliconate was weakening, and the number of cycles of the hydrophobic solution should be less than 3 times.

[0060] Table 2 Water absorption rate of ceramsite treated with different sodium methylsiliconate solution concentrations for 24 hours (%)

[0061]

[0062] Table 3 Water absorption rate of ceramsite treated with sodium methylsiliconate solution for different cycles for 24h (%)

[0063]

[0064] Embodiment 2:

[0065] Prepare sodium methylsiliconate solutions with mass percentages of 2%, 4%, and 6%, respectively, weigh 9 parts of 1 kg of coal gangue ceramsite, immerse the ceramsite in the prepared solution, control the immersion time of 10s, 30min, and 1h, respectively, take it out, let it stand in the filter for 2min to control excess water, then place it in the shade indoors to dry for 3d, and then conduct a water absorption test, completely immerse 1kg of naturally dried silicone impregnated ceramsite in water, take it out at 1h, 3h, 6h, and 24h, respectively, make it saturated surface dry and weigh it according to the water absorption test method in step 4, and calculate its water absorption, such as Figure 1 .Depend on Figure 1 It can be seen that with the increase of the concentration of sodium methylsiliconate solution, the water absorption rate of ceramsite decreased significantly, and the immersion time had little effect on the water absorption rate of ceramsite. There was no significant difference in the water absorption rate of ceramsite immersed for 10 seconds and 1 hour.

[0066] Embodiment 3:

[0067] Untreated ceramsite, 1h pre-wetted ceramsite and ceramsite obtained by organosilicon impregnation treatment in Example 2 were used to completely replace coarse aggregate to prepare ceramsite concrete, and the slump and expansion of concrete were tested. The concrete mix ratio and mixture performance are shown in Table 4. It can be seen that different treatment methods have a significant impact on the working performance of concrete. The slump and slump expansion of the control group (Blank) using untreated ceramsite are 220mm and 620mm respectively, indicating that its fluidity is relatively poor. On the contrary, the ceramsite (PW) pre-wetted for 1 hour significantly improves the fluidity of concrete, and the slump and expansion reach 290mm and 740mm respectively. The improvement of concrete performance by organosilicon impregnation treatment at different concentrations is relatively obvious, with the slump increasing from 265mm to 280mm, and the slump expansion showing an increase from 535mm to 675mm. With the increase of organosilicon concentration, the hydrophobic effect of ceramsite surface is enhanced, which reduces the water absorption rate of ceramsite and thus improves the working performance of concrete.

[0068] After the mixture performance test, 100mm×100mm×100mm cubic specimens were formed, and each group contained 12 specimens. The specimens were cured in a standard curing room under the conditions of 20℃±2℃ and humidity not less than 95%. The compressive strength and splitting tensile strength of the cubes were measured at 7d and 28d of curing. Figure 3 , splitting tensile strength Figure 4 , showing the compressive strength and splitting tensile strength of coal gangue ceramsite concrete with different silicone impregnation concentrations at 7 days and 28 days respectively. Figure 3 It can be seen that the 28-day compressive strength of the OS-6 group reached the highest value, reaching 40.2MPa, which is 118% of the blank group. Compared with the blank group and the pre-wet group, the silicone impregnation treatment OS-2, OS-4, and OS-6 all showed significantly improved compressive strength. Figure 4 The change trend of splitting strength is shown. On the whole, the splitting strength of 28 days is higher than that of 7 days, and the splitting strength of OS-6 group is close to 3MPa. This shows that 6% organic silicon impregnation treatment of ceramsite can significantly enhance the mechanical properties of concrete.

[0069] Table 4 Coal gangue ceramsite concrete mix proportion and mixture properties

[0070]

[0071] Note: Blank is the control group using untreated ceramsite; PW is the ceramsite treated with 1h pre-wetting; "OS-2" means the ceramsite treated with 2% concentration of silicone, and so on.

Claims

1. A method for preparing surface hydrophobic treated coal gangue ceramsite concrete, characterized in that: The steps include: Step 1: prepare a 2-6% by mass organic silicon hydrophobic impregnation solution; Step 2: Weigh an appropriate amount of coal gangue ceramsite and put it into the hydrophobic impregnation solution prepared in step 1 for impregnation; Step 3: Control the immersion time of the gangue ceramsite in the organosilicon impregnation solution to be 10s to 1h; Step 4: Place the impregnated coal gangue ceramsite in the room to dry naturally for 3 days; Step 5: Use the hydrophobic impregnation treated coal gangue ceramsite to completely replace the coarse aggregate to prepare the coal gangue ceramsite concrete.

2. The method for preparing a surface hydrophobic treated coal gangue ceramsite concrete according to claim 1, characterized in that: In step 1, the organic silicon hydrophobic solution used is an aqueous sodium methylsiliconate hydrophobic solution produced by Lianxiang, and its chemical formula is (CH3)3SiONa.

3. The method for preparing a surface hydrophobic treated coal gangue ceramsite concrete according to claim 1, characterized in that: In step 2, the gangue ceramsite is placed in a plastic basket with a filter screen for immersion treatment. The mesh aperture is 3 mm. The physical properties of the gangue ceramsite are a particle size of 5 to 16 mm and a bulk density of 900 to 950 kg / m 3 , apparent density 1300~1330kg / m 3 , 1h water absorption rate 6.0%~6.5%, cylinder pressure strength 5.0~6.0MPa.

4. The method for preparing a surface hydrophobic treated coal gangue ceramsite concrete according to claim 1, characterized in that: In step 3, the gangue ceramsite is impregnated with an organosilicon solution to form a layer of insoluble waterproof polymer compound with a thickness of several molecules on the surface of the ceramsite, i.e., a mesh organosilicon resin film, so that the wetting angle thereof changes from less than 90° to greater than 90°, and the ceramsite changes from hydrophilic to hydrophobic.

5. The method for preparing the surface hydrophobic treated coal gangue ceramsite concrete according to claim 1, characterized in that: In the step 5, the LC30 gangue ceramsite concrete is prepared by mixing the hydrophobic impregnation treated gangue ceramsite, cement, fly ash and fine aggregate; The gangue ceramsite concrete material comprises the following raw materials in parts by weight: 352 parts of cement, 88 parts of fly ash, 660 parts of natural river sand, 560 parts of hydrophobic impregnation treated gangue ceramsite, 145 parts of water, and 2.2 parts of polycarboxylic acid water reducer.

6. The method for preparing the surface hydrophobic treated coal gangue ceramsite concrete according to claim 5, characterized in that: The preparation of coal gangue ceramsite concrete comprises the following steps: mixing cement, fly ash, natural river sand, coal gangue ceramsite treated with hydrophobic impregnation and polycarboxylate water reducer according to a preset ratio, stirring for 30 seconds, then adding water, stirring for 3 minutes, and obtaining the surface hydrophobic treated ceramsite concrete; The vibration time of the surface hydrophobic treated ceramsite concrete during molding should not exceed 5s.

Citation Information

Patent Citations

  • Preparation process of ceramsite with high strength and hydrophobicity

    CN105110810A

  • Water repellent treatment process on ceramic particle surface

    CN1439619A